Fluorescently labeled xylosides offer insight into the biosynthetic pathways of glycosaminoglycans. Issue 60 (29th November 2021) - Mastio, Roberto; Willén, Daniel; Söderlund, Zackarias; Westergren-Thorsson, Gunilla; Manner, Sophie; Tykesson, Emil; Ellervik, Ulf
Abstract : Fluorescently labeled xylosides are taken up by cells and initiate priming of labeled GAG chains of various length. Abstract : Five novel xylosides tagged with the fluorescent probe Pacific Blue™ were synthesized and found to act as substrates for β4GalT7, a bottleneck enzyme in the biosynthetic pathways leading to glycosaminoglycans. By confocal microscopy of A549 cells, we showed that the xylosides were taken up by the cells, but did not enter the Golgi apparatus where most of the glycosaminoglycan biosynthesis occurs. Instead, after a possible double galactosylation by β4GalT7 and β3GalT6, the biosynthesis was terminated. We hypothesize this is due to the charge of the fluorescent probe, which is required for fluorescent ability and stability under physiological conditions.